THE EFFECT OF DIFFERENT HYDROLYSING TIME ON THE PROTEIN HYDROLYZATES OF MUDSKIPPER(Periophthalmusminutus) BY USING ALCALASE ENZYME - Lonika Putri Linda Nainggolan; Edison Edison; Mirna Ilza (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Mudskipper(Periophthalmusminutus) is a type of fish which its habitat was in the muddy shore of the mangrove area.This study aimed to observe the effect of different hydrolysis time on the fish protein hydrolyzate with the addition of alcalase enzymes, to determine the optimum hydrolysis time to produce a high quality of fish protein hydrolyzates, and to describe the characteristics of the fish protein hydrolyzate produced. This research was carried out by making flour and making protein hydrolyzates from mudskipper as a raw material. The method used in this research was the experimental method and composed to a non-factorial Completely Randomized Design (CRD). The treatment conducted wasprotein hydrolyzing the fish in the different time (for 1 hour, 2 hours, and 4 hours) at a temperature of 50 °C, and pH 7.5. The parameters observed were the values of non-protein nitrogen and the content of protein in the fish protein hydrolyzates. The results showed that the protein content in fish flour was 86.56% (db) and water content was 8.85% (wb). The different hydrolyzing time was significantly affecting to the chemical quality of fish protein hydrolyzates. Hydrolyzing fish for 2 hours was the optimum treatment to yield 47.63% fish protein hydrolyzates with the best quality, characterized by the highest content of protein at 7.11% and the value of NPN at 44.39%. Keywords:alcalaseenzym, mudskipper, protein hydrolyzate